Political Friendship, Trust and Democracy: Some Lessons from Recent Theories on Political and Civic Friendship for the Analysis of Democracies and Autocracies - Hayoz, N. (Социология: теория, методы, маркетинг, 2017)
A relational aspect oj political friendship is basically the focus of studies on political friendship looking at informal politics, clientelism or friends in politics, which may be useful on the road to political power. This aspect must, be distinguished from a more general, institutional aspect of political friendship, which political philosophy presents in terms of civic or republican friendship. The idea and the theory of civic friendship deals with aspects of collective action, as well as with those shared norms which are expressed and discussed in the public sphere, the core of the political. In relation to theories of trust,, civic friendship is a civil society, civic and political culture of the practices and expectations in society regarding how to live and how to cooperate. The political theory offriendship is also a warning against the abuse of power and the reintroduction of unity and enemies in a society based on the differences and multiplicity of perspectives.